Tarif Pajak UMKM 0,5% : Reward Or Punishment? - Mutia Indriana; Norsain Norsain; Moh. Faisol (InFestasi, 2020)
Micro, Small and Medium Enterprises (UMKM) become one of the fields for the Directorate General of Taxes to increase the contribution of the amount of tax revenue, considering that as many as 98.8% of business units come from UMKM. One of the tools used to achieve these objectives is the issuance of PP No. 23 of 2018 concerning UMKM taxes of 0.5% of turnover. This research was conducted at KPP Pratama Pamekasan using a case study. As many as one key informants and five supporting informants researchers conducted in-depth interviews (in-depth interview). The information was analyzed qualitatively, consisting of data reduction, data presentation, conclusions, and verification. The results of this study are first, the application of PP No. 23 of 2018 there are still many UMKM that do not know the information, so the Directorate General of Tax (KPP Pratama Pamekasan) needs to socialize it internally. Second, the motive for the application of PP No. 23 of 2018 is as a reward for UMKM taxpayers: as a reward for the convenience given to taxpayers in terms of tax reporting, as a reward for the freedom of taxpayers to choose, and as a reward for the relief of tariffs offered, so taxpayers can fulfill their tax obligations following the provisions of the applicable tax laws.